PENDEKATAN DIAGONAL UNTUK MASALAH PENUGASAN - Zahrotun Mu’alifah; Pardi Affandi; Akhmad Yusuf (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2019)
The assignment problem is a problem related to the optimal assignment of different productive sources that have different levels of efficiency for different tasks. The assignment problem has only one optimization goal, is maximizing or minimizing the resource that use to complete a task. The purpose of this reaserch is to solve the assignment problem with the goal of maximizing or minimizing resource using the steps in the optimal diagonal approach. The steps used in this research with the goal of maximizing resources are looking for two different entries from the assignment cost matrix that has the greatest value of each row and column, whereash the goal of minimizing resource is looking for two different entries from the assignment cost matrix that has value the smallest of each row and column. The results obtained to resolve the assignment problem using an optimal diagonal approach with the goal of maximizing resource, reach the optimal solution if the sum of all diagonal cells is less than zero. While the results to solve the assignment problem with the goal of minimizing resources, reach the optimal solution if the sum of all diagonal cells more than zero. Keywords: Assignment Problem, Transportation Model, Diagonal Optimal Approach